Development of Web-Based Radioactivity Teaching Materials oriented-on Character Education for Highschool Student - Muhamad Gina Nugraha (ASEAN Journal of Science and Engineering Education, 2023)
The development of Information and Communication Technology (ICT) affects the learning process. So, this study aims to produce a product of web-based teaching materials on radioactivity-oriented character education materials that are tested for quality and feasibility and can help teachers and students in learning radioactivity materials. The research used a design-based research model, which used a 3-D technique (i.e. Define, Design, and Develop) to develop teaching materials in this study. The instrument used consisted of a web feasibility judgment sheet in facilitating character education, content feasibility, visual design feasibility, and navigation feasibility used in a limited trial through two stages, namely the expert test stage and the user test. The expert test was conducted by three material and media experts. The user test was conducted by three teachers and 30 students of senior high school students (grade 12). The results of the limited trial overall show that web-based teaching materials are feasible in terms of facilitating character education, content, visual design, and navigation.